New insights on the effect of the H2/CO ratio for enhancement of CO methanation over metal-free fibrous silica ZSM-5: Thermodynamic and mechanistic studies. (1st November 2019) - Hussain, I.; Jalil, A.A.; Mamat, C.R.; Siang, T.J.; Rahman, A.F.A.; Azami, M.S.; Adnan, R.H.
Graphical abstract: Highlights: Metal-free fibrous silica ZSM-5 was successfully synthesized by microemulsion system. Fibrous morphology enhanced pore volume, oxygen vacancies and basicity of FSZSM-5. CO methanation was greatly improved by H2 /CO ratio in order of 1:5 > 1:3 > 1:2 > 1:1. Comparatively, experimental results were near to thermodynamic results. Abstract: Thermodynamic and experimental facts of CO methanation were conducted by the Gibbs energy minimization method to produce substituted natural gas (SNG). The microemulsion technique was used to synthesized metal-free fibrous silica ZSM-5 (FSZSM-5) to compare with the catalytic activity results with the thermodynamic results. The catalysts were characterized by FESEM, TEM, XRD, BET, FTIR, and ESR. While spent catalysts were evaluated by TGA/DTA, TEM, EDX, and Raman spectra to study the change in morphology and carbon deposition. In-situ FTIR spectroscopy was used to investigate the possible reaction mechanism. The FSZSM-5 was proved the best catalyst than ZSM-5 due to unique fibrous morphology, high BET surface area (610 m 2 /g), high basicity, and extensive oxygen vacancies. The FSZSM-5 exhibited a higher CO methanation activity of 56% CO conversion and 78% CH4 selectivity using H2 /CO = 5:1 at 450 °C. Increasing the H2 : CO ratio favored methanation activity to produce CH4 and to resist carbon deposition in the following order: 5:1 > 3:1 > 2:1 > 1:1. Furthermore, the in-situ FTIR results supported the proposal that the dissociation of linear adsorbed CO over oxygen vacancies appeared to control the rate of CH4 formation by hydrogenation of adsorbed C*. These results will be beneficial to understand better and optimize the CO methanation reaction process in the preparation of highly active catalysts for SNG production.